1999
DOI: 10.1136/fn.81.1.f5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of behaviour disorders in low birthweight infants

Abstract: Aim-To compare the prevalence of childhood and adolescent behavioural problems in low birthweight infants with matched controls. Methods-A cohort study of a geographically defined population of survivors of <1500 g birthweight born in 1980 and 1981 and age, sex, and school matched controls was undertaken. Children with a clinical disability were excluded. Data from Rutter questionnaires, completed by parents and teachers when the children were aged 8 and again at age 14 years, were assessed. Results-From an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 23 publications
1
36
1
Order By: Relevance
“…e.g., [15,16,[24][25][26][27][28][29][30]. Varying prevalence estimates can be attributed to differences in population denominators and sample sizes.…”
Section: The Preterm Behavioural Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…e.g., [15,16,[24][25][26][27][28][29][30]. Varying prevalence estimates can be attributed to differences in population denominators and sample sizes.…”
Section: The Preterm Behavioural Phenotypementioning
confidence: 99%
“…Almost all studies using screening measures, such as those outlined above, have found significantly increased rates of behaviour problems in very preterm or VLBW adolescents. Using a cut-off for the risk of clinically significant problems, typically defined as scores >90 th percentile of a standardisation sample or that of matched controls, authors have reported a 3-8 fold increased risk for behavioural problems compared with term-born peers.e.g., [15,16,[24][25][26][27][28][29][30]. Varying prevalence estimates can be attributed to differences in population denominators and sample sizes.…”
mentioning
confidence: 99%
“…Behavioral and emotional problems have been reported in VLBW children at 8 and 14 years of age, 57 13 to 14 years of age, 22 and 12 to 16 years of age on parent ratings. 29 The overall risk of behavior disorder in the VLBW population has been estimated at 2% to 3% 57 ; however, in our perinatally higher risk cohort, we found a much higher prevalence.…”
Section: Behaviormentioning
confidence: 99%
“…This method provides a coherent view of the complete metabolic response of organisms to physiological and pathophysiological stimuli. Preterm birth is associated with increased risk of neurological disorders [23,24] including cerebral palsy [25], mental retardation [26,27], learning difficulties [28][29][30] and behavioural problems [31]. The aetiology of preterm birth is related to premature membrane rupture in 30% of cases, to maternal and foetal indication for early pregnancy termination in 20-25% of cases and to spontaneous preterm births in about 40-45% of cases [32].…”
Section: Introductionmentioning
confidence: 98%